Reduced bulk and surface states densities in metal‐induced crystallized polycrystalline silicon nanowires. Issue 11 (26th October 2016) - Le Borgne, B.; Pichon, L.; Thomas, M.; Salaün, A. C.
Abstract : Polycrystalline silicon nanowires are fabricated following sidewall spacer approach using conventional UV lithography technique. Unfortunately, solid phase crystallization of nanowires implies low electrical properties due to the poor nanowires crystal quality. As polycrystalline silicon nanowires based field effect transistors find a lot of applications, improving nanowires crystalline quality is a technological challenge. One solution studied here is metal induced lateral crystallization method, using nickel as catalyst to create oriented crystals. The comparison is done between these two crystallization techniques. Indeed, we deeply investigate silicon nanowires/insulator interface and nanowires qualities by the determination of the energy distributions of the densities of states and the surface states using the Suzuki's incremental method. This calculation confirms that metal induced lateral crystallization significantly reduces bulk and surface states densities, compared to solid phase crystallized nanowires.